PELATIHAN PRAKTIKUM KELAS KIMIA SKALA KECIL UNTUK GURU KIMIA DENGAN TOPIK REAKSI NETRALISASI DI KOTA MAGELANG - Hapsari, Natalia Diyah; Pamenang, Fransisca Ditawati Nur; Cristy, Liana Vinca Rosea; Ferdiansyah, Nikolas Noel; Nathasya, Paschalia Melinda (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Chemistry learning integrates three components, microscopic, macroscopic, and symbolic. However, during the Corona Virus Disease-19 (COVID-19) pandemic, which lasted approximately two years, it caused delays in the learning process that integrated microscopic, macroscopic, and symbolic components, resulting in a decline in students' understanding. Therefore, community service brings new insights to chemistry teachers in Magelang city and introduces learning activities through small chemistry courses on acid-base titration materials with the theme of neutralization reactions.  This training was conducted by 2 lecturers and 3 students offline at SMAS Tarakanita Magelang. Based on the results of the satisfaction rating, 71.23% of the participants answered that it was very useful and 28.7% of the participants thought it was useful.